How dehumanization leads to murder and genocide lessons from the Nazi era - Gabel, Stewart 1943- (Academic Studies Press, 2023)
"This book discusses psychological aspects of dehumanization and of the human tendency to dominate, control and potentially murder those considered less than or "other" by the dominant group. It explores how increasingly severe dehumanization resulted in the genocide of six million Jews in the second World War. Psychological and behavioral strategies Nazi aggressors and ordinary citizens used to mislead themselves during this process are described. Understanding the sequence of events from dehumanization to murder has implications for the apparent tendency of human beings to harm and potentially kill those who appear "different", or who are made into the "other". Efforts to prevent genocide should actively challenge dehumanization of weaker populations whenever possible, even when dehumanization appears mild, "insignificant" or "innocuous.""
Includes bibliographical references and index
Keywords: Entmenschlichung; Völkermord; Genocide / Psychological aspects; Murder / Psychological aspects; Nazis / Psychology